More Evidence Pertaining to "Their Females" in Romans 1:26. - MURPHY, DAVID J. (Journal of Biblical Literature)
According to the standard view, the "females" of Rom 1:26b have sexual intercourse with other females. According to an older interpretation, however, they engage in nonprocreative sex with men. In this article, I present hitherto unnoticed material in support of the latter interpretation. First, when χρῆσις/χράομαι ("use") denotes a sex act, its subject is the man, and the context involves penetration. It is doubtful that χρῆσις in Rom 1:26b refers to female-female sex. Second, I cite three additional ancient writers who deem male-female nonprocreative sex "unnatural." Third, discrepant views among earlier Byzantine writers (Anastasius, Arethas, and Greek redactors of Pseudo-Methodius's Apocalypse) reinforce how the female-female interpretation was not the prevailing one in the early centuries. Fourth, linguistic features of Rom 1:27a more readily support the anal-oral interpretation than the female-female interpretation.